Competency-Based Medical Education implementation: Are we transforming the culture of assessment?. (3rd July 2019) - Griffiths, Jane; Dalgarno, Nancy; Schultz, Karen; Han, Han; van Melle, Elaine
Abstract: Purpose: Adopting CBME is challenging in medicine. It mandates a change in processes and approach, ultimately a change in institutional culture with stakeholders ideally embracing and valuing the new processes. Adopting the transformational change model, this study describes the shift in assessment culture by Academic Advisors (AAs) and preceptors over three years of CBME implementation in one Department of Family Medicine. Methods: A qualitative grounded theory method was used for this two-part study. Interviews were conducted with 12 AAs in 2013 and nine AAs in 2016 using similar interview questions. Data were analyzed through a constant comparative method. Results: Three overarching themes emerged from the data: (1) specific identified shifts in assessment culture, (2) factors supporting the shifts in culture, and (3) outcomes related to the culture shift. Conclusions: In both parts of the study, participants noted that assessment took more time and effort. In Part 2, however, the effort was mitigated by a sense of value for all stakeholders. With support from the mandate of regulatory bodies, local leadership, department, faculty development and an electronic platform, a cultural transformation occurred in assessment that enhanced learning and teaching, use of embedded standards for performance decisions, and tracking and documentation performance.